THE IMPACT OF BILINGUALISM ON ENGLISH LANGUAGE ACQUISITION - Raximova Feruzabonu Shodlikbek qizi; Ne'matova Madina Baxtiyor qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the impact of bilingualism on English language acquisition, focusing on how speaking two or more languages influences cognitive development, linguistic awareness, and communication skills. Bilingualism is increasingly recognized as an asset in language learning, as it enhances metalinguistic awareness and facilitates the acquisition of additional languages like English. However, it can also present challenges such as interference, code-switching, and uneven language proficiency. The article discusses both the advantages and difficulties of bilingualism in learning English, emphasizing that bilingual learners possess unique linguistic flexibility that can accelerate their mastery of English when properly supported by educational strategies.